Գրիգոր Մարաշեցու մատենագրական վաստակը - Թերզյան, Գայանե (Մատենադարան)
Grigor Marashets‘i is a distinguished 12th century author, philosopher and monk. Three works by him, the “Woe Book”, “Confession of Sins,” and “On the Day of Death” have reached us and are kept in Mashtots Matenadaran as well as in the repositories of Jerusalem, Venice and Vienna (about 22 manuscripts). The themes of his spiritual-lyrical works are self-criticism, remorse, and confession. The text of his lengthy colophon from Ms M108 is cited in the article. Григор Марашеци – автор 12-ого века, известный философ и вардапет, живший и творивший в пустыне Есванц в Киликии. Из его произведений до нас дошли «Վայ Գիրք» (“Книга о горе”), «Մեղաներ» (“Исповедание грехов”) и «Վասն աւուր մահուան» (“O смертном дне”). Произведения Григора Марашеци хранятся как в Матенадаране (Институт древних рукописей им. Месропа Маштоца), так и в рукописных хранилищах Иерусалима, Венеции, Вены (около 22 рукописей). Его духовно-лирические произведения основаны на раскаянии и исповедании грехов. В статье приводится текст пространного колофона автора из рукописи М 108.
Keywords: Պատմաբանասիրություն